Microalbuminuria in Metabolic Obesity: A Cross-Sectional Study in a Selected Tertiary Care Hospital of Bangladesh - Sultana, Sharmin; Rahman, Md Matiur; Saha, Rinky Rani; Ahad, Md Golam; Shila, Jakia Sultana; Khan, Md Aminul Haque (Journal of Enam Medical College, 2022)
Background: Overweight and obese individuals may have no cardiometabolic risk whereas normal weight individuals may present with cardiometabolic risk. The term‘Metabolic obesity’ has been floated to identify hidden metabolic risks irrespective of BMI. The pathophysiology of metabolic obesity can be explained by microvascular dysfunction and microalbuminuria is a wellknown marker of microvascular dysfunction. Objective: The objective of this study was to find out the association of microalbuminuria with metabolic obesity in Bangladeshi adult subjects. Materials and Methods: This cross- sectional analytical study included 200 individuals who attended outpatient department in Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from March 2018 to February 2019. The study subjects were divided into metabolically obese (metabolically unhealthy) group and metabolically non-obese (metabolically healthy) group by metabolic syndrome (MetS) criteria. Metabolic syndrome was defined according to the South Asian Modified-National Cholesterol Education Program (NCEP). Microalbuminuria was defined as a urinary albumin to creatinine of 30 to 300 mg/gm. Demographic profile, BP, height, weight, waist circumference etc. were measured and fasting blood glucose, serum triglyceride, serum HDL-C were estimated and albumin to creatinine ratio (ACR) was calculated. Statistical analysis was done using SPSS version 22.0. Results: The frequencies of metabolically obese (metabolically unhealthy) group and metabolically non-obese (metabolically healthy) group were 128 (64%) and 72 (36%) respectively. Mean values for age (p value 0.001), body mass index (p value 0.027), waist circumference (p<0.001), systolic blood pressure (SBP) (p<0.001) and diastolic blood pressure (DBP) (p<0.001), fasting blood glucose (p<0.001) and triglycerides (p<0.001) were significantly higher in the metabolically obese group compared to metabolically non-obese group. Among the study subjects, the prevalence of microalbuminuria was 32.5% and prevalence of microalbuminuria was found very high (38.3%) in metabolically obese group, whereas microalbuminuria in metabolically non-obese group was found 22.2%, which was statistically significant (p value 0.02). Our results showed that diastolic BP (p<0.001), systolic BP (p<0.001), fasting blood sugar (p<0.001) and triglyceride (p<0.008) were significantly correlated with microalbuminuria. In the logistic regression analysis, diastolic BP (p value 0.015) and FBS (p value 0.039) were significantly associated with microalbuminuria. After harmonization of statistical analysis, our study indicated that elevated blood pressure and fasting blood sugar had strong association with microalbuminuria and are likely to be critical components that lead a substantial number of subjects to the prestage of metabolic obesity in the Bangladeshi adult population. Conclusion: Our study concludes that the prevalence of microalbuminuria is significantly high in metabolic obesity (metabolically unhealthy) in Bangladeshi adult population. Association of microalbuminuria with metabolic obesity is mainly attributed to high diastolic blood pressure and fasting blood glucose. J Enam Med Col 2020; 10(3): 159-168